The Impact of Online Game Addiction on Student’s Attention - Aryani Pamukti; Fathul Lubabin Nuqul; Shinta Nuriya Idatul Alfain; Rohmatul Hannani (Universitas Darussalam Gontor, 2024)
Generally, research on online game addiction only focuses on children or adolescents whose learning patterns still need to be better organized. However, this research focuses on students expected to have a more regular learning pattern. This is because not all students have academic achievements that are as expected. Some students who enter the class play online games with laptops or gadgets. This study aimed to determine online game addiction among santri students, determine the level of attention among santri students, and the effect of online game addiction on attention among santri students. This study uses a quantitative approach. The subjects of this study were santri students with active status in Islamic boarding schools based on Islamic boarding schools. Data collection in this study used an online game addiction scale and a Stroop test to measure attention. The analysis test in this study used the help of the R program. Based on the hypothesis test using the R program, it shows that online game addiction significantly affects the attention of santri students. The results of the research data analysis show that students who get high online game addiction scores have low attention scores. Conversely, students who have low online game addiction scores have high attention scores. This proves that there is an influence of online game addiction on attention . One way to increase attention so that students do not experience addiction to online games, namely by replacing student energy or energy substitution , for example, with sports activity programs.